Weedy rice invasion in fields of India and management options - Jose, Nimmy; Abraham, C. T.; Rathore, Meenal (Indian Farming, 2018)
Weedy rice has emerged as a dominant weed species and majorthreat to rice production in traditional rice belts of the country. Itemerges faster than cultivated rice and develops vigorous root systems and competes with rice for nutrients, light, water, and other plant growth resources. Weedy rice causes 34 to 75% reduction in direct seeded rice depending upon its intensity. Integration of different management options like higher seed rate, use ofpigmented rice varieties, appropriate tillage practices, adoption of mechanized transplanting or dibbling, scientific water management, and hand weeding are the effective management options formanagement of weedy rice.